Repair of an Extensive Defect of the Ear and Retroauricular Scalp. Issue 4 (2nd April 2023) - Shahwan, Kathryn T.; Demer, Addison M.; Maher, Ian A.
Abstract : Supplemental Digital Content is Available in the Text.